A Multiparametric Clinical and Echocardiographic Score to Risk Stratify Patients with Chronic Systolic Heart Failure: Derivation and Testing. Issue 10 (6th June 2013) - Fontanive, Paolo; Miccoli, Mario; Simioniuc, Anca; Angelillis, Marco; Bello, Vitantonio Di; Baggiani, Angelo; Bongiorni, Maria Grazia; Marzilli, Mario; Dini, Frank Lloyd
<x xml:space="preserve">Abstract</x> Although echo Doppler and biomarkers are the most common examinations performed worldwide in heart failure (HF), they are rarely considered in risk scores. In outpatients with chronic HF and left ventricular ejection fraction (LVEF) ≤45%, data on clinical status, echo Doppler variables, aminoterminal pro‐type B natriuretic peptide (NT‐proBNP), estimated glomerular filtration rate (eGFR), and drug therapies were combined to build up a multiparametric score. We randomly selected 250 patients to produce a derivation cohort and 388 patients were used as a testing cohort. Follow‐up lasted 29 ± 23 months. The univariable predictors that entered into the multivariable Cox model were as follows: furosemide daily dose >25 mg, inability to tolerate angiotensin converting enzyme (ACE) inhibitors, inability to tolerate β‐blockers, age >75 years, New York Heart Association (NYHA) >2, eGFR<60 mL/min, NT‐proBNP plasma levels above the median, tricuspid plane systolic excursion (TAPSE) ≤14 mm, LV end‐diastolic volume index (LVEDVi) >96 mL/m2, moderate‐to‐severe mitral regurgitation (MR) and LVEF <30%. The scores of prognostic factors were obtained with the respective odds ratio divided by the lower odd ratio: 4 points for furosemide dose, 3 points for age, NT‐proBNP, LVEDVi, TAPSE, 2 points for inability to tolerate β‐blockers, inability to tolerate ACE inhibitors, NYHA, eGFR<60 mL/min, moderate‐to‐severe MR, 1 point for LVEF. The multiparametric score predicted all‐cause mortality either in the derivation cohort (68.4% sensitivity, 79.5% specificity, area under the curve [AUC] 78.7%) or in the testing cohort (73.7% sensitivity, 71.3% specificity, AUC 77.2%). All‐cause mortality significantly increased with increasing score both in the derivation and in the testing cohort (P < 0.0001). In conclusion, this multiparametric score is able to predict mortality in chronic systolic HF.